Geochemistry of high‐Nb basalt‐andesite in the Erguna Massif (NE China) and implications for the early Cretaceous back‐arc extension. (15th March 2018) - Liu, Huichuan; Li, Yinglei; Wu, Liwen; Huangfu, Pengpeng; Zhang, Ming
Abstract : This paper presents new zircon laser ablation–inductively coupled plasma–mass spectrometry U–Pb age and whole‐rock geochemical data for the high‐Nb basalts‐andesites (HNBs) from the Meiletu Formation in NE China. In comparison with common arc basalts and Nb‐enriched basalts, the Meiletu HNBs (140 Ma) show high TiO2 (1.7–3.2 wt.%), P2 O5 (0.7–1.7 wt.%), Nb (14.6–34.0 ppm), and Zr (314–600 ppm) contents, and high (Nb/Th)PM (0.26–0.91), (Nb/La)PM (0.22–0.36), Nb/U (8.2–24.8) ratios. They show strongly light rare earth element (REE) enriched chondrite‐normalized REE patterns with unusually high total REE contents [(TREE)cn = 978–1802]. Unlike adakite‐associated HNBs derived from a mantle wedge metasomatized by adakites, the Meiletu HNBs were derived from low degree (<2%) partial melting of the garnet peridotite at considerable depth (>80 km). The Meiletu HNBs were generated in an intracontinental back‐arc extension setting. Combined with previous geological observations, it is argued that Early Cretaceous tectonics of the Erguna Massif is dominated by the Mongol–Okhotsk oceanic slab‐rollback and back‐arc extension.